2020
DOI: 10.1109/tnsm.2020.2976838
|View full text |Cite
|
Sign up to set email alerts
|

Network Function Offloading Through Classification of Elephant Flows

Abstract: With the move from traditional hardware appliance based network functions to Network Function Virtualization, software development is decoupled from the hardware. However, as a network function is no longer optimized for hardware, beneficial features of networking hardware may not be used any more. Solutions such as SDN or NIC offloading aim to overcome this antipodes by integrating networking hardware into the packet processing pipelines. On the one hand, offloading traffic of network functions to hardware ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…CacheFlow [17] constructs a directed acyclic graph model to identify and analyze dependencies between rules, employing either the Dependent-Set Algorithm or the Cover-Set Algorithm to determine which rules should be cached in hardware. LFP [18] proposes a method for network function offloading, blending sampling and machine learning to decide on hardware node offloading based on initial flow packet predictions. OVS-CAB [7] presents an offloading mechanism for Open vSwitch on smart network interface cards, addressing rule overlap issues effectively.…”
Section: Related Workmentioning
confidence: 99%
“…CacheFlow [17] constructs a directed acyclic graph model to identify and analyze dependencies between rules, employing either the Dependent-Set Algorithm or the Cover-Set Algorithm to determine which rules should be cached in hardware. LFP [18] proposes a method for network function offloading, blending sampling and machine learning to decide on hardware node offloading based on initial flow packet predictions. OVS-CAB [7] presents an offloading mechanism for Open vSwitch on smart network interface cards, addressing rule overlap issues effectively.…”
Section: Related Workmentioning
confidence: 99%
“…In contrast, our primary objective is to identify a flow as rapidly as possible, ideally from its first packet. Durner et al in [20] demonstrated flow classification on the first packet, using only features extracted from the 5-tuple (src IP, dst IP, src port, dst port, protocol) and the size of the first packet. In [21] Hardegen et al suggested multiclass prediction as an alternative to binary classification (elephant/mouse), employing a deep neural network to predict flow characteristics from the 5-tuple of the first packet.…”
Section: Related Workmentioning
confidence: 99%
“…Durner et. al. proposes to distribute traffic between NICs and the host according to flow characteristics [6]. Flex-Gate [19] proposes to offload proper functionalities among diverse ones to the NIC and the remaining are on the end host.…”
Section: Related Workmentioning
confidence: 99%